Cairo Traffic Congestion Study : Final Report - World Bank (Washington, DC, 2014)
The Greater Cairo Metropolitan Area (GCMA), with more than 19 million inhabitants, is host to more than one-fifth of Egypt's population. The GCMA is also an important contributor to the Egyptian economy in terms of GDP and jobs. The population of the GCMA is expected to further increase to 24 million by 2027, and correspondingly its importance to the economy will also increase. Traffic congestion is a serious problem in the GCMA with large and adverse effects on both the quality of life and the economy. In addition to the time wasted standing still in traffic, time that could be put to more productive uses, congestion results in unnecessary fuel consumption, causes additional wear and tear on vehicles, increases harmful emissions lowering air quality, increases the costs of transport for business, and makes the GCMA an unattractive location for businesses and industry. These adverse effects have very real and large monetary and nonmonetary costs not only for the economy of the GCMA, but given its size, for the economy of Egypt as well. As the population of the GCMA continues to increase, traffic congestion is becoming worse and the need to address this congestion is becoming more urgent. In recognition of the seriousness of the problem of traffic congestion, and upon the request of Government, primarily the Ministries of Finance, Transport, Housing, and Interior, the World Bank funded an investigation into its magnitude, causes, and potential solutions in the GCMA. This report documents the results of the study. The results of this study should be of interest to policy-makers and practitioners in the GCMA, the Egyptian Government, other cities facing similar problems, and international financial institutions.